LUCIANA DURANTI and PATRICIA C. FRANKS, eds., Encyclopedia of Archival Science - Ilerbaig, Juan (Archivaria, 2016)
Encyclopedia of Archival Science. LUCIANA DURANTI and PATRICIA C. FRANKS, eds. Lanham, MD: Rowman & Littlefield, 2015. x, 454 pp. ISBN 978-0-8108-8810-4.